Effets de l’usage d’une application mobile sur l’exploration touristique du centre historique d’Albi - Jan Smolinski; Cédric Calvignac (Netcom)
Our survey aims at observing how mobile technologies change the way visitors explore a touristic area. It focuses mainly on the way tourists use a dedicated mobile application during their trip and follow or not its guidelines. To investigate the use of such a mobile device, we conducted a survey whose methodology consisted in generating digital traces (GPS coordinates, browsing history) and collecting users’ feedback (semi-directed interviews). We observed 2 different visitors groups: 8 couples using a paper booklet (comprised of a tourist information leaflet and a city map), and 8 couples with the same equipment plus a smartphone application. Comparing these 2 distinct groups enables us to assess the effects of using a mobile application on the course of the visit. We will see that using this digital device alter in many ways tourists’ pace, direction and information processing.